STRATEGY FOR THE UTILIZATION OF METAL-ORGANIC FRAMEWORKS (MOFS) IN REMOVAL OF DYE FROM TEXTILE INDUSTRY - Mareta, Fahru
The most used synthetic dyes in the textile industry are the dyes which hard to degrade in nature, the dyes can be harmful to the environment if they are thrown into the river without any teratment. However, conventional watertreatment method like sedimentation or bioremediation are unable to remove the dyes from the water. Some alternative methods such as using an absorbent, advanced oxidation porcesses (AOPs), or membrane have potential in removal of dyes in the wastewater treatment. One of the interesting matreials for this application is metalorganic frameworks (MOFs) because it has high surface area (up to 7800 m2/g; six times of active carbon surface area), high porosity, and flexibility in design of its structure. As an absorbent, MOFs can absorb metyl orange (MO) as dye model, 40 times higher than active carbon. As a catalyst, MOFs can degrade dye five times faster than semiconductor such as TiO2. And MOFs as a membrane has higher permeability than any of conventional membrane. However, the performance of MOFs in dye waste treatmen still can be enhanced through modification of its structure. Therefore, in this research, performance of MOFs in dye waste treatment have been studied to evaluate the strategies to improve the performance of MOFs in dye waste treatment and will be presented in three parts: MOFs as absorbents, MOFs as catalysts, and MOFs as membrane. Factors such as surface area, selectivity of MOFs, catalytic or photocatalytic activity, and stability of the MOFs have been discussed. In addition, will be discussed the potential and future prospect of MOFs in dye waste treatment.